Edible Oils and Development of New Products: Sensory, Microbiological, and Cytotoxic Aspects - do Espírito Santo de Jesus, Fabiane; de Jesus Freitas, Tayane; Bispo, Alana M.; de Matos Santos, Lívia; Braga Alves, Agnes Sophia; Aparecida Souza Machado, Bruna; Ferreira Ribeiro, Camila Duarte (Current Organic Chemistry, 2023)
Edible oils offer several health benefits. Their inclusion in food products can improve the nutritional profile while reducing saturated and trans fats. This research aimed to evaluate the sensory, microbiological, and cytotoxic characteristics of edible oils and analyze how these characteristics behave when oils are added to food products. A comprehensive search of scientific articles was conducted in the databases and virtual libraries DOAJ, IOP Science, MDPI, Scopus, SpringerLink, Taylor & Francis Online, and Wiley Online Library, using a time frame from 2000 to 2023. Fish oils and oil blends were widely used in these studies. The analyzed studies demonstrated satisfactory results regarding flavor, appearance, and overall acceptance of edible oils. Low microbial growth was also found, and no toxicity was reported in the studies. Among the 70 studies reviewed, a substantial majority (76%) introduced edible oils into food formulations, focusing on dairy, baked, and confectionery products. Most of the studies that applied oils in foods showed no significant difference (p > 0.05) in attributes such as color, texture, aroma, and overall acceptance compared to products without oil addition (control). Encapsulation techniques for oils and the incorporation of flavorings were identified as effective strategies for seamlessly integrating edible oils into food products. Considering the importance of the characteristics of edible oils, this study can encourage, and support researchers interested in exploring this field and developing innovative oil-based food products.
Keywords: encapsulation